2017
DOI: 10.1111/aor.12884
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Dialysis of Cytokine-Rich Plasma With High and Medium Cut-Off Membranes Reduces Its Procalcific Activity

Abstract: Recently developed high-flux (HF) dialysis membranes with extended permeability provide better clearance of middle-sized molecules such as interleukins (ILs). Whether this modulation of inflammation influences the procalcific effects of septic plasma on vascular smooth muscle cells (VSMCs) is not known. To assess the effects of high cut-off (HCO) and medium cut-off (MCO) membranes on microinflammation and in vitro vascular calcification we developed a miniature dialysis model. Plasma samples from lipopolysacch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Evidence of potential benefit is growing rapidly. In small studies to date, dialysis with MCO membranes has been associated with a reduction in the activation of the renin-angiotensin system (47), reduced serum concentrations and expression of proinflammatory cytokines (TNF-a and IL-6) (48), and reduced induction of vascular calcification (49).…”
Section: Clinical Evaluation Of Mco Dialyzersmentioning
confidence: 99%
“…Evidence of potential benefit is growing rapidly. In small studies to date, dialysis with MCO membranes has been associated with a reduction in the activation of the renin-angiotensin system (47), reduced serum concentrations and expression of proinflammatory cytokines (TNF-a and IL-6) (48), and reduced induction of vascular calcification (49).…”
Section: Clinical Evaluation Of Mco Dialyzersmentioning
confidence: 99%
“…In prolonged therapy period, the plasma levels of immune-modulatory proteins such as TNF-receptor 1, lambda and kappa free light chain also tend to decrease. In addition, the calcification of vascular smooth muscle cells is significantly lower after incubation with HRO/MCO-and HCO-serum compared to HF plasma in vitro [22] . In contrast, lipoprotein-associated phospholipase A2 were elevated obviously after receiving HDx therapy [19] .…”
Section: Medium Cut-off/high Retention Onset Membrane and Expanded DImentioning
confidence: 89%
“…The process of identification, selection, screening and inclusion of the studies are depicted in Figure 1. The following studies were included: MGP [12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42]; OC [9,10,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69]; Gas6 [70,71,72,73,74,75,76,77,78,79,80,8...…”
Section: Methodsmentioning
confidence: 99%
“…Willy et al [30] found that serum samples from patients after High Cut-Off dialysis (HCO) have a reduced capacity to induce in vitro calcification in VSMCs compared to patients after conventional High Flow dialysis (HF). A possible explanation of this decline in pro-calcifying activity could be that, after incubation with serum from HF, VSMCs produced considerably higher anti-calcifying proteins (e.g., MGP) than VSMCs incubated in HCO or Medium Cut-Off dialysis (MCO) serums, as a compensatory response to the augmented calcification environment.…”
Section: Vkdps In Kidney Diseasementioning
confidence: 99%